No. 1 2-SON DEKABR, 2025 -YIL INDUSTRIAL TOURISM IN UZBEKISTAN: COMPREHENSIVE ANALYSIS OF THE READINESS OF UZBEKISTAN ENTERPRISES TO RECEIVE VISITORS (Marketing Journal, 2025)
The article presents the results of a comprehensive analysis of enterprises from various regions of the Republic of Uzbekistan conducted by the Research Institute for Tourism Development within the applied project “Industrial Tourism: Trends and Prospects for Development in Uzbekistan.” The study summarizes the findings of a sociological survey of more than 100 enterprises aimed at assessing their readiness to develop industrial tourism. The research covers enterprises from different industrial and service sectors and includes an assessment of human resources, infrastructure, organizational capacity, and excursion readiness. The article identifies key regional differences, target audiences, and systemic barriers, and proposes mechanisms for the development o f industrial tourism as an independent sector of the economy. The results indicate a growing interest of enterprises in participating in industrial tourism, creating prerequisites for the formation of new tourism clusters and the implementation of educatio nal and cultural -cognitive programs.
Keywords: industrial tourism; excursion programs; infrastructure readiness; regional development; tourism potential; Uzbekistan